The chemistry of oxygen - Ebsworth, E. A. V. (Pergamon texts in inorganic chemistry, 1973)
The Chemistry of Oxygen provides a comprehensive coverage of the structure, properties, behavior, and chemical reaction of oxygen. The title first details the general information on oxygen, such as the history, occurrence, and various properties. Next, the selection deals with oxygen atoms and ions. Chapter 3 talks about oxide as a class, while Chapter 4 covers the physical and chemical properties of water. The text also details various compounds that have oxygen, such as oxygen fluorides and hydrogen peroxide. The ninth chapter covers the ozone and its related species, and the last chapter di.